Structure-guided design of anti-cancer ribonucleotide reductase inhibitors. (1st January 2019) - Misko, Tessianna A.; Liu, Yi-Ting; Harris, Michael E.; Oleinick, Nancy L.; Pink, John; Lee, Hsueh-Yun; Dealwis, Chris G.
Abstract: Ribonucleotide reductase (RR) catalyses the rate-limiting step of dNTP synthesis, establishing it as an important cancer target. While RR is traditionally inhibited by nucleoside-based antimetabolites, we recently discovered a naphthyl salicyl acyl hydrazone-based inhibitor (NSAH) that binds reversibly to the catalytic site (C-site). Here we report the synthesis and in vitro evaluation of 13 distinct compounds (TP1-13 ) with improved binding to hRR over NSAH (TP8 ), with lower KD 's and more predicted residue interactions. Moreover, TP6 displayed the greatest growth inhibiting effect in the Panc1 pancreatic cancer cell line with an IC50 of 0.393 µM. This represents more than a 2-fold improvement over NSAH, making TP6 the most potent compound against pancreatic cancer emerging from the hydrazone inhibitors. NSAH was optimised by the addition of cyclic and polar groups replacing the naphthyl moiety, which occupies the phosphate-binding pocket in the C-site, establishing a new direction in inhibitor design.